(untitled) (Journal of Universal Science Research, 2025)
Pilonidal sinus pathology is prevalent among young adult populations and demonstrates a high rate of recurrence subsequent to surgical management. Despite the availability of various operative techniques, recurrence continues to contribute to increased healthcare utilization and patient morbidity. The present investigation aims to delineate both intrinsic (patient-specific) and extrinsic (procedure-related) variables statistically associated with recurrence following surgical intervention for pilonidal sinus disease.